EDUKASI CUCI TANGAN SEBAGAI BAGIAN PERILAKU HIDUP BERSIH DAN SEHAT PADA SISWA SALAFIYAH ULA (SU) ISLAMIC CENTER BINBAZ - Isti Antari; Yuanita (ABDIMAS Madani, 2019)
The period of elementary school children is one of the times when playing is one of their daily activities. The hand is the area most that is often in contact with objects around when playing, where this allows for germs to stick and enter the body through food so that it can cause disease. Purwandari et al (2015) mention hand-washing behavior related to diarrhea (Purwandari, 2015). The results of the preliminary study indicates that the first grade students of SU of Islamic Center Binbaz who already know about the correct hand washing procedures are less than 10%. In connection with these results, community service activities related to clean and healthy living behavior were focused on training of the correct hand washing procedures, with stages of providing counseling about clean and correct living behavior, socializing on how to do 6 steps hand washing according to WHO and demonstrating proper hand washing by students. The service activities increased the level of students' knowledge of how to wash their hands properly became 80%.